Nursing care in anesthetic-surgical positioning (Research, Society and Development, 2021)
One of the concerns of the nursing team refers to the positioning of the patient during surgery, as the problems caused by inadequate anesthetic-surgical positioning in health institutions represent one of the greatest compromises to the patient's health. The main objective of the study was to describe the main nursing care during anesthetic-surgical positioning and more specifically, to describe the risk factors for injury in anesthetic-surgical positioning. It is a bibliographic review with a descriptive and qualitative approach, which used the databases of Google Scholar, VHL (virtual health library) and SciELO (Scientific Electronic Library Online). The research resulted in a final sample of 65 articles, which allowed a better understanding of the appropriate surgical positioning. It is up to the nurse to plan and implement care, as well as specific care for the ideal anesthetic-surgical position. It was observed that the nurse's actions are directly related to the management of the team, mainly technicians and assistants who will manipulate the patient. When positioning the patient on the operating table, in addition to ensuring patient safety, the team must make sure that the surgical area is well exposed, with the body well aligned and that the pressure at the highest tension points has adequate protection. It was possible to observe a shortage of national publications on the subject addressed in this study. A greater understanding of the topic contributes to mitigate the risks related to anesthetic-surgical positioning.